Energetics and equilibrium properties of thin pseudomorphic si1-xcx(100) layers in si - Kaxiras, Efthimios; Kelires, Pantelis C. (My University, 1997)
We investigate the structure of carbon enriched thin silicon films which involve large strains, using first-principles total energy calculations and Monte Carlo simulations. We identify the energetically most favored configurations of substitutional carbon atoms in the Si(100) surface layers, and obtain the equilibrium depth profile at various temperatures. The interplay between the reconstruction strain field and the solute-atom interactions leads to complicated structural patterns that are different from related weakly strained systems.
Keywords: Carbon; Silicon; Thin films; Temperature